2022
DOI: 10.18502/ajmb.v14i4.10484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PLGA-Encapsulated Recombinant GroEL of S. typhi immune Responses Against Enterohaemorrhagic and Enteropathogenic Escherichia coli

Abstract: Background: Heat Shock Proteins (HSPs) elicit humoral and cellular immune responses. Due to their high sequence homology, they can be developed as a new immunogen for cross prophylactic and vaccination effects against infectious agents such as Enteropathogenic and Enterohemorrhagic Escherichia coli (EPEC and EHEC). This study aimed to evaluate the immunogenicity and cross-protective efficacy of rGroEL of Salmonella typhi (S. typhi) encapsulated in poly lactic-co-glycolic acid (PLGA) nanoparticles against EPEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition, as the cytoplasmic membrane plays a vital role in prokaryotic cells viability, this membrane destruction can cause cell death [44]. Recent studies have shown that bacterial isolates, including E. coli, are highly resistant to common antibiotics such as cefixime [45,46]. A high rate of resistance was reported for cefixime (57.9%) on E.coli isolated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the cytoplasmic membrane plays a vital role in prokaryotic cells viability, this membrane destruction can cause cell death [44]. Recent studies have shown that bacterial isolates, including E. coli, are highly resistant to common antibiotics such as cefixime [45,46]. A high rate of resistance was reported for cefixime (57.9%) on E.coli isolated.…”
Section: Discussionmentioning
confidence: 99%